Wasatiyyah Islam in The Framework Pesantren Education Tradition - Hasan, Mohammad (Institut Agama Islam Negeri Madura, 2018)
Islamic boarding schools are religious institutions that not only teach religious problems to santri, but also relate to the role of porndok pesantren on community empowerment. Islamic boarding schools also have a role in national politics. In this context the role of the pesantren in dialogue and contextualizing Islamic teachings is not rigid and black and white. But Islamic boarding schools are able to display the teachings of Islam that are harmonious, peaceful, tolerant, and not radical. Islamic understanding initiated by Islamic boarding schools is far from the values of radical doctrines, or easy doctrine to state ‘heresy’ to other groups. This becomes the view and value championed by the pesantren community including the role of the Kiai (Islamic clergy) in developing modern and global life.